THE UNVEILING OF THE FIRST IRANIAN WOMAN, TÁHIRIH QURRATU'L- `AYN, IN THE MID-19TH CENTURY - Nasim Kamali, (IJRDO- Journal of Educational Research, 2025)
Táhirih Qurrat al-ʿAyn (1814–1852) was the first woman in the mid-19th century in Iran who asserted her voice in thepatriarchal society. She advocated for gender equality boldly, publicly challenged social norms, and fought for women’srights. Tahirih emerged within the Bahá'í Faith and, with her powerful and impactful poetry during the time of social andpolitical upheaval, dismantled traditional gender rules. This paper contextualizes and examines her influence within thesocial and political landscape of her time and examines her influence on the early feminist movement in Iran and herlasting impact on the discussion surrounding gender equality. The unveiling of Táhirih Qurrat al-ʿAyn represents not justa personal act of defiance but a significant moment in the broader struggle for women's rights, symbolizing the enduringquest for emancipation and equality in the face of oppression. By analyzing her writings and the historical circumstancesthat cultivated her activities, this paper seeks to reveal the complexities of Táhirih’s legacy and her significance in bothIranian and global feminist thought